Company valuation methods: applying dynamic analogical-atock market valuation models to agrarian co-operatives - Vidal Gimenez, F.=700 1 Sales Civera, J.M.; Lopez Lluch, D.B.
(Es, En)
ilus., 16 ref.
Keywords: MODELOS DINAMICOS; BODEGAS; COOPERATIVAS; ESPAÑA; VALOR COMPLEMENTARIO DE FUSION